Extramedullary hematopoiesis and paraplegia in a patient with hemoglobin e-Beta thalassemia (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):452-7The abstract of this article is available on the PubMed website